KELAYAKAN USAHA PENGOLAHAN EKSTRAK DAUN GAMBIR (Uncaria gambir Roxb) OLEH PETANI LOKAL DI KABUPATEN LIMA PULUH KOTA, SUMATERA BARAT - Widya Fitriana; Wetri Febrina (Jurnal Industri Hasil Perkebunan, 2023)
The development of agricultural commodity processing innovations continues to be pursued to encourage agriculture down streamin. Gambier is a plant that has the potential to be processed into a health drink because it contains high polyphenols. It is hoped that this simple processing technique can be applied by the local community as an alternative for a prospective health drink business. This study aims to (1) find out the technical processing of the Gambier into Gambier herbal tea; (2) analyze the financial feasibility of the business. The analytical method used is descriptive qualitative and quantitative with four financial feasibility indicators, namely Net Present Value (NPV), Benefit Cost (B/C) Ratio, Internal Rate of Return (IRR) and Payback Period (PP). The results showed that Gambier plant processing into Gambier leaf herbal tea had a yield of 25 percent and a positive NPV value of 1,479,239. The B/C value is greater than one, which is 1.013. The IRR value above the prevailing interest rate is 7.47 percent and PP is lower than the investment age, which is 17.1 percent. Overall this business is financially viable. Strengthening these businesses needs to be done as an alternative micro-small industry that can improve the local economy.